The syntax of interjections in isiXhosa: A corpus-driven study - Andrason, Alexander; Matutu, Haile (Stellenbosch Papers in Linguistics Plus, 2019)
This paper examines the syntactic properties of interjections in isiXhosa and their compliance with the interjectional prototype and its extra-systematicity as postulated in linguistic typology. By reviewing nearly two thousand uses of interjections in the comic genre, the authors conclude the following: in its integrity, the category of interjections is internally complex and diversified, containing members with varying degrees of canonicity and extra-systematicity. Although in various uses interjections comply with the interjectional prototype, and being extra-systematic in many others, their canonicity and extra-systematicity are significantly lower.